Regenerative Roles of the Cyclooxygenase-2 Pathway in Neovascularization and Stem Cell Regulation: A Brief Perspective from In Vitro and In Vivo Studies - Melati Puspadewi; Syarifah Dewi (Biomedical Journal of Indonesia, 2026)
Cyclooxygenase-2 (COX-2) is a key enzyme in prostanoid production and is best known as a mediator of the inflammatory response. Beyond this well-established role, COX-2 also contributes to tissue regeneration by promoting neovascularization and supporting stem cell recruitment, proliferation, and differentiation. Despite this, research on harnessing the COX-2 pathway as a therapeutic tool, rather than solely as a target for inhibition, remains limited, presenting a promising avenue for future studies. In this review, we summarize current insights from both in vitro and in vivo models into COX-2 signaling in tissue regeneration, focusing on molecular mechanisms through which its downstream mediators, especially prostaglandin (PGE2), regulate vascular formation, tissue growth, and stem cell function. We also briefly outline the dual nature of these processes, which can either facilitate repair or drive pathological outcomes, and discuss emerging strategies for achieving controlled therapeutic applications.